IMPLEMENTATION OF ISLAMIC BOARDING SCHOOL-BASED EDUCATIONAL MANAGEMENT TO IMPROVE STUDENT DISCIPLINE AND INDEPENDENCE - Asep Supriatna; Warsali Warsali; Saepudin Saepudin; Susilawati Susilawati; Agus Jaenal (Indonesian Journal of Islamic Studies (IJIS), 2026)
Islamic boarding school-based educational management is a relevant character development model in facing the challenges of moral degradation and low student independence in the modern era. This study aims to analyze the implementation of Islamic boarding school-based educational management at SMPIT Manbaul Ulum in improving student discipline and independence. The research approach used is a qualitative case study. Data were obtained through in-depth interviews, participatory observation, and documentation studies, which were then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the implementation of Islamic boarding school-based educational management is carried out through the integration of religious values in all school activities, consistent regulation of discipline, habituation of congregational worship, and strengthening student personal responsibility through independence programs. Student discipline is increased through structured supervision and positive behavioral habits, while independence grows through assignments that encourage self-management and independent decision-making. These findings prove that the Islamic boarding school-based educational management model is effective in shaping students' disciplined and independent character. The implications of this study indicate that the Islamic boarding school-based approach can be an alternative educational management strategy that focuses not only on academic achievement, but also on character development.